User-friendly [(diglyme)NiBr2]-catalyzed direct alkylations of heteroarenes with unactivated alkyl halides through c?h bond cleavages - Ackermann, Lutz; Punji, Benudhar; Song, Weifeng (Advanced Synthesis & Catalysis, 2011)
A nitrogen and phosphorus ligand-free catalytic system derived from inexpensive [(diglyme)NiBr2] allowed for efficient direct C[BOND]H bond alkylations of heteroarenes with unactivated β-hydrogen-containing alkyl halides under basic reaction conditions.

Cobalt-catalyzed C–H bond functionalizations with aryl and alkyl chlorides - Punji, Benudhar; Song, Weifeng; Shevchenko, Grigory A.; Ackermann, Lutz (Chemistry - A European Journal, 2013)
Inexpensive cobalt catalysts derived from N-heterocylic carbenes (NHC) allowed efficient catalytic C[BOND]H bond arylations on heteroaryl-substituted arenes with widely available aryl chlorides, which set the stage for the preparation of sterically hindered tri-ortho-substituted biaryls. Likewise, challenging direct alkylations with β-hydrogen-containing primary and even secondary alkyl chlorides proceeded on pyridyl- and pyrimidyl-substituted arenes and heteroarenes. The cobalt-catalyzed C[BOND]H bond functionalizations occurred efficiently at ambient reaction temperature with excellent levels of site-selectivities and ample scope. Mechanistic studies highlighted that electron-deficient aryl chlorides reacted preferentially, while the arenes kinetic C[BOND]H bond acidity was found to largely govern their reactivity.